KAJIAN HUKUM DAN REGULASI TERKAIT SERANGAN HACKING PADA PLATFORM DIGITAL DI INDONESIA - Adelina Damayanti; Rina Arum Prastyanti (PT. Jurnal Center Indonesia Publisher, 2024)
Hacking is a technique carried out by someone (hacker, cracker, intruder, or attacker) to attack a system, network, and application by exploiting weaknesses with the intention of gaining access rights to data and systems. Currently, the development of Information and Communication Technology (ICT) is experiencing very rapid growth. The development of information technology, especially the internet, has provided many positive benefits for its users. However, the use of internet technology also has negative impacts that cannot be ignored. The increase in Cybercrime cases in Indonesia is also caused by the impact of advances in Information Technology. Based on this explanation, the aim of this research is to find out how to study law enforcement procedures for hacking victims on digital platforms and how to ensure that digital platform users are more regulated regarding cyber security. The research method used is a descriptive analytical method. The results and discussion in this research are that handling crime cases in the field of information and electronic transactions is a responsibility that has been established for investigators, especially cyber patrols, to investigate and uncover these crimes. The investigation process has a very important and strategic role in determining the success of criminal law enforcement. The quality of a good investigation greatly determines the possibility of success in the prosecution process and makes it easier to reveal material truths during the trial. In order to prevent cybercrime, it is important for individuals and governments to have a deep understanding of crime patterns in the digital realm as well as current and ongoing internet trends and behavior carried out by perpetrators of these crimes. Keywords : Hacking, cyber, digital platform